The Power of Digital Marketing Tools: Case study of PT Lifa Plasmet Indonesia - Lady, Lady; Defen, Defen; Qadri, Rizni Aulia (Oikonomia: Jurnal Manajemen, 2025)
Purpose The development of increasingly modern times makes all business activities use digital marketing to increase brand awareness of a business. PT Lifa Plasmet Indonesia is a company in the field of manufacturing plastic ID accessories and product customization decided to do digital marketing with sites, Facebook and Instagram social media, create Mailchimp, and create a trade account on the Tokopedia marketplace site. Methodology The research method used is descriptive qualitative with a data triangulation approach through interviews, observation and documentation. Findings The results in this study show an impressive positive impact in gaining public awareness about PT Lifa Plasmet Indonesia through websites or sites and social media. These results can be seen from the number of website visits, insights from Facebook and Instagram social media, as well as increased customer reviews and interactions on Google My Business. Suggestion It is hoped that the company will remain consistent in maintaining the content uploaded on social media and maximizing the increased exposure of PT Lifa Plasmet Indonesia